MENINGKATKAN MINAT, MOTIVASI, HASIL BELAJAR LOMPAT JAUH MELALUI BOLA GANTUNGMENINGKATKAN MINAT, MOTIVASI, HASIL BELAJAR LOMPAT JAUH MELALUI BOLA GANTUNG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study is to increase interest, motivation and student learning outcomes in the long jumpfollowing learning styles through media Hang Style hanging balls. This research is a classroom action research.This study uses 2 cycles, where each cycle consists of: 1) planning, 2) implementation of the action; 3)observation; 4) reflection. The results showed that the learning outcomes of the long jump with media style styleball hangs suspended in class VIII A SMP N 1 Randublatung Blora positive impact as seen on masterylearning outcomes of students who exceed predetermined KKM is 75 increased namely in the first cyclecompleteness studied at 73, 53% while in the second cycle reached 91.18% mastery learning. It is concludedthat learning style hangs long jump style by using the media hanging balls have a positive effect, which canincrease student interest and motivation shown by the average response of students who stated that attractedand interested in learning methods so that they become motivated and interested to learn.